Oculomotor Nerve Palsy as a Presenting Symptom of Epstein-Barr Virus-Associated Infectious Mononucleosis: Case Report and Review of the Literature - Leon Amadeus Steiner (Karger Publishers, 2021)
Primary Epstein-Barr virus (EBV) infection is the main cause of infectious mononucleosis (IM), which typically presents with a triad of fever, lymphadenopathy, and tonsillar pharyngitis in young adults. In contrast, neurological manifestations of IM are rare. We report on a 23-year-old man with subacute oculomotor nerve palsy followed by symptoms of IM 6 days later. Primary EBV infection was confirmed by PCR detection of EBV DNA in blood as well as by subsequent serology. High-resolution magnetic resonance imaging revealed an edematous change at the root exit zone and gadolinium enhancement of the right oculomotor nerve as well as pial enhancement adjacent to the right ventral mesencephalon. A review of the literature identified 5 further patients with isolated oculomotor nerve palsy as the presenting symptom of unfolding primary EBV infection. MRIs performed in 3 of those 5 patients revealed a pattern of contrast enhancement similar to that of the present case. This case report and literature review highlight that, although rare, IM should be considered in the differential diagnosis of oculomotor nerve palsy in young adults.